ANALISIS KELAYAKAN USAHATANI TEBU (Studi Kasus Petani Tebu Mitra PG.Pakis Baru di Kecamatan Tayu Kabupaten Pati) - -Eka Dewi Nurjayanti; Syaifun Naim (MEDIAGRO, 2014)
PG Pakis Baru is a company that implement systems partnership with sugarcane farmers in some regions. Partnership applied is PG as credit guarantor for partner farmers. There are several requirements that must be met by sugarcane farmers to become partner farmers. The first requirement is the farmer must submit a certificate of ownership to PG.Pakis Baru as collateral. Next, the farmer is required to submit a harvest before becoming partner farmers. The quality of the harvests as farmers non-facility determines the amount of loans granted PG.Pakis Baru to partner farmers. Not only the credit facility, PG.Pakis Baru also provide a quota of subsidized fertilizer and counseling sugarcane cultivation to farmers. At the time of milling, partner farmers will obtain molasses, waste or leftovers from sugarcane milling process, which can be used alone or sold. Sugarcane cultivation that run by partner farmers in Tayu District Pati Regency spend costs up to IDR 25.610.211,00. These costs consist of fixed costs worth IDR 9.788.892,00 and variable costs worth IDR 15.832.319,00. Fixed cost component consists of cost of land rental and tax costs. Labor costs, the cost of fertilizers (ZA and Ponska), and the cost of transport is a component of variable costs. Revenue of sugarcane farming amounted to IDR 40.601.262,82 was obtained from the sale of harvests and molasses. Based on that revenues and expenses, the farmers obtained income IDR 14.991.051,82. Sugarcane farming in Tayu District Pati Regency feasible to be developed based on the criteria of R-C ratio and the BEP. R-C values obtained ratio 1,59 and BEP IDR 16.983.416,44 or in quantity 44.454,55 kg. Keywords: sugarcane, feasibility, partnership